The Impact of Sand Mining on the Environment in Tamedan Village, North Dullah Island District, Tual City - Ren-El, Sridevi; Riry, Johan; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study aims to determine the impact of sand mining activities on the environment in Tamedan Village, Pulau Dullah Utara District, Tual City. This research method uses a descriptive method with a quantitative and direct field approach. The population in this study was the Tamedan Village community both directly involved in mining and those affected by sand mining. The variables in this study consist of sand mining activities (X) and environmental damage (Y). Data collection techniques in this study were conducted through observation, interviews, filling in questionnaires, and documentation, while for data analyzing data using descriptive statistics and inferential analysis. Bassed on theprocessed data, it is known that the independent variabel (X), namely sand mining activities, has an effect on the dependent variabel (Y) , namely environmental damage, determined based on the significant value in the results the value obtained is 0,001 < 0,05, which means that the variabel X has an effect on the variabel Y. the process of mutual influence, namely sand mining on environmental damage, the higher the number of sand mines, the higher the environmental damage in Tamedan Village, North Dullah Island District Tual City